Isolation and Characterization of Mutations in the Escherichia coli Regulatory Protein XapR - Jørgensen, Casper (American Society for Microbiology, 1999)
In this work, the LysR-type protein XapR has been subjected to a mutational analysis. XapR regulates the expression of xanthosine phosphorylase (XapA), a purine nucleoside phosphorylase in Escherichia coli. In the wild type, full expression of XapA requires both a functional XapR protein and the inducer xanthosine. Here we show that deoxyinosine can also function as an inducer in the wild type, although not to the same extent as xanthosine. We have isolated and characterized in detail the mutants that can be induced by other nucleosides as well as xanthosine. Sequencing of the mutants has revealed that two regions in XapR are important for correct interactions between the inducer and XapR. One region is defined by amino acids 104 and 132, and the other region, containing most of the isolated mutations, is found between amino acids 203 and 210. These regions, when modelled into the three-dimensional structure of CysB from Klebsiella aerogenes, are placed close together and are most probably directly involved in binding the inducer xanthosine.